Comparative Study of the Quality of Life and cost-Effectiveness Between Patients Treated with Helicobactor Pylori Eradication and Acid Suppression therapy in Duodenal Ulcer Disease - Chowdhury, M; Bhuiyan, MMR; Hossain, J; Majumder, TK; Raihan, A; Roy, RK; Hasan, M (Medicine Today, 2012)
DOI: http://dx.doi.org/10.3329/medtoday.v23i2.13098 Medicine TODAY Vol.23(2) 2011 pp.67-71